ENTREPRENEURSHIP AND INNOVATION: FOCUSING ON THE ROLE OF ENTREPRENEURSHIP IN DRIVING INNOVATION AND ECONOMIC GROWTH - Azizakhon Sanakulova Sherali qizi (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract. This article explores the essential role of entrepreneurship in fostering innovation and driving economic growth. In an era characterized by rapid technological change and global competitiveness, entrepreneurship is no longer merely associated with starting new businesses; it has become a core engine of innovation, productivity, and national development. Entrepreneurs introduce new ideas, processes, and technologies that challenge existing norms, create new markets, and generate employment opportunities.The paper analyzes how entrepreneurship contributes to innovation-led growth by examining theoretical foundations, global experiences, and the case of Uzbekistan. Drawing upon Schumpeter's theory of creative destruction and contemporary studies, the article highlights how entrepreneurial ecosystems stimulate economic dynamism and adaptability in the face of modern challenges. In the context of Uzbekistan, the study reviews recent policy reforms, innovation hubs such as IT Park, and youth-led startup initiatives supported by governmental and private institutions.